Awareness, knowledge, and practices related to diabetic retinopathy among diabetic patients in primary healthcare centers at Riyadh, Saudi Arabia - Manal H AlHargan (Journal of Family Medicine and Primary Care, 2019)
Context: Diabetic retinopathy (DR) is a microvascular complication for diabetes mellitus (DM), with around 35% of diabetic patients developing some form of DR. Aims: This study assessed the awareness toward DR, practice of regular eye examination, and DM control among diabetic patients. Settings and Design: This was a cross-sectional study among diabetics at two primary healthcare centers in Riyadh, Saudi Arabia, who were selected by convenience sampling. Methods and Materials: The questionnaire contained sections for demography, knowledge, attitude, and practice toward DR, and compliance to DM treatment. The association of awareness about retinopathy with demographics was compared. Statistical Analysis Used: The association of awareness about retinopathy and education level with demographics and compliance with treatment were compared using Chi-square test. Results: In total, 280 diabetic patients were included, 187 (67%) were males, mean age was 58.9 ± 10.1 years, and median duration of diabetes was 10 years. There was good awareness about DR, diabetes was well controlled in 170 (61%) patients, but less than half (45%) had their eyes checked within 1 year. Patients with education level of high school and above had higher awareness than those with no formal education (P < 0.001). Also, those with income level >10,000 SR had higher awareness than those with income ≤5,000 SR (P < 0.05). Conclusion: There was high awareness among the diabetic patients regarding DR but annual check-up was done in less than half of the patients. Improvement is required for scheduling annual eye examinations for the early detection of DR.